Higher Density Environments and the Critical Role of City Streets as Public Open Spaces - Wen, Liang; Kenworthy, Jeff; Marinova, Dora (MDPI AG, 2020)
This paper explores the relationship between crowding and streets as public open spaces in high-density urban environments from the perspectives of perceived density and human needs, two antecedents to crowdedness. City streets are the places through which various forms of crowding are perceived and experienced. Hence, they can play a role in easing this sense of crowding if corresponding strategies are put in place. The paper argues that practices, such as traffic calming and self-building, can transform the streets to serve as public open space, which increases spaciousness and eases crowding. It also puts forward tactical urbanism as a strategy for city governance to create the right conditions encouraging flourishing civil society initiatives in a dense primary environment that is invigorating and at the same time has a level of crowding perceived as both comfortable and liveable.